Potency of Intraguild Predation to Disrupt the Optimum Functions of Predatory Arthropods: An Ecological Perspective - Nugroho Susetya Putra (Jurnal Perlindungan Tanaman Indonesia, 2006)
Some empirical studies have revealed the ecological consequence of interspecific relationships among predatory arthropods that is the disruption of natural functions of indigenous species of predators on their preys, i.e. phytophagous arthropods. In relation to many efforts on the utilization of introduced species of natural enemies, particularly predatory arthropods, the effects oflntraguild Predation (IGP) on key predators should be considered carefully to optimize their potency. In addition, understanding the impact of biological traits of each species of predatory arthropods on their ability to adapt from being predated by other species might be important to predict their composition and possibilities for being exist in ecosystem.